The functions of languagem and the understanding of mental disorders // As funções da linguagem e o entendimento das desordens mentais - Bucca, Antonino (CONJECTURA: Filosofia e Educação, 2014)
<!–[if gte mso 9]> Normal.dotm 0 0 1 108 619 111111 5 1 760 12.0 <![endif]–><!–[if gte mso 9]> 0 false 14 18 pt 18 pt 0 0 false false false <![endif]–><!–[if gte mso 9]> <![endif]–> <!– /* Style Definitions */ p.MsoNormal, li.MsoNormal, div.MsoNormal mso-style-parent:""; margin:0cm; margin-bottom:.0001pt; mso-pagination:widow-orphan; font-size:12.0pt; font-family:"Times New Roman"; mso-fareast-font-family:"Times New Roman"; mso-bidi-font-family:"Times New Roman"; @page Section1 size:612.0pt 792.0pt; margin:70.85pt 2.0cm 2.0cm 2.0cm; mso-header-margin:36.0pt; mso-footer-margin:36.0pt; mso-paper-source:0; div.Section1 page:Section1; –> <!–[if gte mso 10]> <mce:style><! /* Style Definitions */ table.MsoNormalTable mso-style-name:"Tabella normale"; mso-tstyle-rowband-size:0; mso-tstyle-colband-size:0; mso-style-noshow:yes; mso-style-parent:""; mso-padding-alt:0cm 5.4pt 0cm 5.4pt; mso-para-margin:0cm; mso-para-margin-bottom:.0001pt; mso-pagination:widow-orphan; font-size:12.0pt; font-family:"Times New Roman"; mso-ascii-font-family:Cambria; mso-ascii-theme-font:minor-latin; mso-fareast-font-family:"Times New Roman"; mso-fareast-theme-font:minor-fareast; mso-hansi-font-family:Cambria; mso-hansi-theme-font:minor-latin; –> <!–[endif] –> <!–StartFragment–>Indeed, linguistic schizophrenic characteristics seem very different from those related to paranoiac language. Numerous studies on schizophrenic language documents describe an expressive and cognitive universe that is away from the sense and meaning of paranoiac madness. Language, then, becomes the mirror of psychotic experience and interpretation of objective, subjective and intersubjective reality. In this paper, considering characteristics of schizophrenic glossolalia (schizophrenic language use) and considering paranoiac need to rhetorical language (inherently argumentative and persuasive), we’ll try to bring out some differences (cognitive, linguistic, psychopathological, ontological) between psychosis schizophrenic and paranoiac ones.<!–EndFragment–>